Suppression of FOXP3 expression by the AP-1 family transcription factor BATF3 requires partnering with IRF4 - Arnold, Preston R.; Wen, Mou; Zhang, Lei; Ying, Yuanlin; Xiao, Xiang; Chu, Xiufeng; Wang, Guangchuan; Zhang, Xiaolong; Mao, Zhuyun; Zhang, Aijun; Hamilton, Dale J.; Chen, Wenhao; et al. (Frontiers in Immunology, 2022)
FOXP3 is the lineage-defining transcription factor for Tregs, a cell type critical to immune tolerance, but the mechanisms that control FOXP3 expression in Tregs remain incompletely defined, particularly as it relates to signals downstream of TCR and CD28 signaling. Herein, we studied the role of IRF4 and BATF3, two transcription factors upregulated upon T cell activation, to the conversion of conventional CD4+ T cells to FOXP3+ T cells (iTregs) in vitro. We found that IRF4 must partner with BATF3 to bind to a regulatory region in the Foxp3 locus where they cooperatively repress FOXP3 expression and iTreg induction. In addition, we found that interactions of these transcription factors are necessary for glycolytic reprogramming of activated T cells that is antagonistic to FOXP3 expression and stability. As a result, Irf4 KO iTregs show increased demethylation of the critical CNS2 region in the Foxp3 locus. However, we also show that BATF3 and IRF4 play critical roles to iTreg function, demonstrating unique roles for these transcription factors in FOXP3 induction vs. in differentiated iTregs. Thus, our findings highlight how BATF3/IRF4 interactions contribute to the complex interplay between TCR signaling, FOXP3 expression and stability, and iTreg function while providing important insights to cellular mechanisms that govern expression of the Foxp3 locus.